2022
DOI: 10.3389/fcell.2022.982663
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early life maternal deprivation on the perineuronal nets in the prefrontal cortex and hippocampus of young adult rats

Abstract: Early life stress negatively impacts brain development and affects structure and function of parvalbumin immunopositive (PV+) inhibitory neurons. Main regulators of PV+ interneurons activity and plasticity are perineuronal nets (PNNs), an extracellular matrix formation that enwraps PV+ interneurons mainly in the neocortex and hippocampus. To experimentally address the impact of early life stress on the PNNs and PV+ interneurons in the medial prefrontal cortex and dorsal hippocampus in rats, we employed a 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The loss of parvalbumin-positive interneurons was reported in the olfactory cortex of a similar APP/PS1 double transgenic mouse model ( 16) and electrophysiological deficits in PV-positive cortical interneurons were found (17). Additionally, selective vulnerability of PVpositive interneurons has been documented under different experimental conditions, including epilepsy (18), global ischemia (19), IL6 overexpression (20) and schizophrenia (21,22). In our study there were no indication of the loss of parvalbumin-positive interneurons in the hippocampus, based on the immunostaining pattern, thus it is rather the loss of axons and/or synaptic terminals that occurs in APPPS1 mice.…”
Section: Discussionmentioning
confidence: 90%
“…The loss of parvalbumin-positive interneurons was reported in the olfactory cortex of a similar APP/PS1 double transgenic mouse model ( 16) and electrophysiological deficits in PV-positive cortical interneurons were found (17). Additionally, selective vulnerability of PVpositive interneurons has been documented under different experimental conditions, including epilepsy (18), global ischemia (19), IL6 overexpression (20) and schizophrenia (21,22). In our study there were no indication of the loss of parvalbumin-positive interneurons in the hippocampus, based on the immunostaining pattern, thus it is rather the loss of axons and/or synaptic terminals that occurs in APPPS1 mice.…”
Section: Discussionmentioning
confidence: 90%
“…Like in our study, they showed that GABAergic and extracellular maturation corresponds with major changes in neurocircuitry and plasticity. New evidence showing that early life stress alters perineuronal nets that play important role stabilizing synaptic inputs to developing inhibitory interneurons ( Guadagno et al, 2021 ; Jakovljević et al, 2022 ). Maternal deprivation, as a model of early life stress, also affects the physiology of the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%
“…In all these structures, structure volume, number of principal neurons as well as interneurons were decreased ( Aksić et al, 2014 , 2021 ), and the evidence for the increased oxidative stress were found ( Marković et al, 2017 ). Additionally, the number and structure of perineuronal nets around PV+, as well as PV-neurons were altered in the lymbic cortex, but not in the hippocampus ( Jakovljević et al, 2022 ). These findings are accompanied by reduced cholinergic input to those structures, as well as overall loss of dopaminergic neurons in the substantia nigra and ventral tegmental area ( Marković et al, 2014 ; Kapor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNNs have been reported to be altered in conditions such as early life stress [23], schizophrenia [24], Alzheimer's disease (AD) [25], ischemia [26,27], and Rett syndrome [28]. In fact, the dysfunction or disruption of PNNs in the hippocampus has been associated with the modulation of memory [29], highlighting their essential role in higher cognitive functions.…”
Section: Introductionmentioning
confidence: 99%